Sarah Morris - CAPITAL letters read better for initials (August Verlag, 2015)
Sarah Morris creates paintings and films that explore urban codes and power structures. Her graphic, diagrammatic paintings employ rigorous abstraction to create a virtual architecture that plays with notions of social space and identity. Frédéric Paul explores themes such as power, architecture, geometry and manipulation in Morris' complementary practices of painting and film.